SO DE VITAMINAS PARA A PRODUÇÃO DE FORRAGEM HIDROPÔNICA DE AVEIA - SANT’ANA, Gabriela Rodrigues; VENDRUSCOLO, Eduardo Pradi; CARRASCO, Gilda; REBOLLEDO, Pabla; MARTINS, Murilo Battistuzzi (ANAIS DO ENIC, 2025)
-